Kenyamanan Warga Belajar Paket C di Sanggar Kegiatan Belajar (SKB) Kota Pekanbaru - Pratama, Rido; Achnad, Said Suhil; Fitrilinda, Dafetta; Ayub, Daeng (Journal of Education Religion Humanities and Multidiciplinary, 2024)
This research is descriptive research with a quantitative approach. Descriptive research is research conducted to determine the value of independent variables, either one or more variables (independent) without making comparisons or connecting one variable with another. The data collection method in this research is observation and questionnaires. This research instrument goes through several stages, namely: 1) Examining all theories related to the variables to be studied, 2) Compiling indicators from the variables, 3) Compiling a grid, 4) Compiling statement items and establishing a measurement scale, 5) test try the instrument, 6) analyze the question items by testing the validity and reliability of each statement. Based on the conceptual definition, the comfort indicators in this research are 1) adjustment, 2) harmony with the room, 3) calm conditions, and 4) feelings that depend on the situation. The data in this research were analyzed using descriptive statistical data analysis and One-way ANOVA analysis. Based on the comfort of residents studying Package C at the Pekanbaru City Learning Activities Studio (SKB), it is classified as very high with a mean of 4.07 and a standard deviation value of 0.74. By obtaining the following mean indicators: 1) self-adjustment by obtaining a mean of 4.05 with a standard deviation value of 0.73 with a very high interpretation, 2) harmony with the room with a mean value of 4.12 with a standard deviation value of 0.71 with very high interpretation, 3) calm conditions with a mean value of 4.06 with a standard deviation value of 0.74 with a very high interpretation, 4) feelings that depend on the situation with a mean value of 4.08 with a standard deviation value of 0.78 with an interpretation very high.